THE POLITICS OF TRUTH: ON LEGAL FETICHISM AND THE RHETORIC OF COMPLEMENTARITY - Naftali, Patricia (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2015)
This paper questions the rhetoric of complementarity between truth commissions and criminal courts in the light of the normalization of a “right to truth” in international legal discourse. Once regarded as mutually exclusive institutions, they are now praised by the international community, human rights and transitional justice advocates as complementary in the fight against impunity. This paper reveals, beyond the consensus on complementarity, how the competition between truth commissions and criminal justice continues as truth advocates strive to negotiate the contours of the “right to truth” in international law. First, it highlights the role of global promoters of the “right to truth” in consolidating the theory of complementarity before international bodies. However, it then stresses their competing visions of complementarity and examines the tensions surrounding the normalization of the “right to truth” in relation to criminal justice and amnesties. Finally, it discusses why these tensions are nonetheless accommodated through the discourse on complementarity, especially in the context of an emerging “truth order” and globalized truth “industry” characterized by the rise of new types of expertise, practices and truth-seeking technologies concerned with the ascertainment and adjudication of mass atrocities.